Cardiac remodeling during the neonatal intensive care period; a window of opportunity for early prevention of heart failure?. (December 2020) - Le, Nhu; Phad, Nilkant; de Waal, Koert
Abstract: Background: There is growing evidence that preterm birth is a risk factor for early heart failure as a result of cardiac remodeling during a critical period of growth and development. The aim of this study was to explore if cardiac remodeling can be detected very early after preterm birth, and if present, if those remodeling changes persist until discharge. Methods: Echocardiography parameters of left ventricular geometry and function were prospectively obtained with echocardiography in preterm infants <30 weeks gestation at postnatal day 3 and at 36 weeks postmenstrual age (PMA). Findings were compared to available data of healthy fetuses and cardiac remodeling was classified based on changes in left ventricular volume and/or mass. Results: 65 (37 male) preterm infants were analysed. Three days after birth, 27.7% of infants had abnormal LV geometry, with immaturity and fetal growth restriction as risk factors for these early cardiac remodeling changes. At 36 weeks PMA, after a median period of 9 weeks of neonatal intensive care, 69.2% had abnormal cardiac geometry which could be classified as dilated hypertrophic remodeling (50.0%), dilated remodeling (11.5%) and hypertrophic remodeling (7.7%). Conclusion: Cardiac remodeling changes can be detected very early after preterm birth. However, most changes take place during the neonatal intensive care period. The findings of this study could assist in identifying a group where an early and short-term intervention has the potential to prevent a pathway of abnormal cardiac development. Highlights: Preterm birth is associated with an interruption of normal cardiac development. This form of cardiac remodeling has been labelled cardiomyopathy of prematurity. Cardiac remodeling after preterm birth is a risk factor for early heart failure in adulthood. Most cardiac remodeling takes place during the neonatal intensive care period. The neonatal period provides a window of opportunity for prevention of early heart failure.